The Impact and Prospects of Green Chemistry for Textile Technology - Ul-Islam, Shahid, editor 649511; Butola, Bhupen Singh, editor 649512; ScienceDirect (Online service) 7722 (Duxford : Woodhead Publishing, 2019)
The Impact and Prospects of Green Chemistry for Textile Technology provides a review and summary of the role of green chemistry in textiles, including the use of green agents and sustainable technologies in different textile applications. The book systematically covers the history and chemistry of eco-friendly colorants, chitin, chitosan, cyclodextrin, biomordants, antimicrobial, UV protective, flame retardant, insect repellant textiles, and advanced pre- and post- treatment technologies, such as the sonochemistry and plasma methods currently employed in functional modifications. The book also pays attention to the remediation of textile effluents using novel, sustainable and inexpensive adsorbents. Written by high profile contributors with many years of experience in textile technology, the book gives engineers and materials scientists in the textile industry the information they need to effectively deploy these green technologies and processes.